The role of SIRT2 in alpha-tubulin, Tau and alpha-synuclein post-translational modifications in parkinson's disease - Palma, Andreia Filipa Martins (2015)
Trabalho final de mestrado integrado em Medicina (Biologia Molecular), apresentado à Faculdade de Medicina da Universidade de Coimbra.